Modern Japan$1 (Bs Place in World Historys From Meiji to Reiwa - Yamauchi, Masayuki; Hosoya, Yuichi; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This Open Access book includes chapters on the key turning points in modern Japanese history from the Meiji Restoration to Japan-China diplomatic normalization in the 1970s and beyond. The topics covered include the First Sino-Japanese War, the Russo-Japanese War, the First and Second World Wars, the Manchurian Crisis, the US Occupation, postwar Japan-China relations, and postwar decolonization. Readers will learn how new research by Japanese historians has led to the revision of conventional views on the turbulent history of Japan, once the enemy of the United States in the war in the Asia-Pacific and now the US$1 (Bs closest ally in the region. Historical research on the modern history of Japan has been constantly updated. From the Meiji Restoration to the present day, Japan has experienced the effects of modernization and globalization. Recent historical inquiries in Japan tend to focus on the merging of modern history with global history. During the past 150 years, Japan has never been separated from events in international affairs. Scholars and general readers will appreciate the new factual details and philosophical perspectives that this volume provides drawing on the work of fourteen authors who are recognized leaders in their fields. Yuichi Hosoya is Professor of International Politics at Keio University. Masayuki Yamauchi is Specially Appointed Professor at the Musashino University Institute for Global Affairs and Professor Emeritus, the University of Tokyo.s
Chapter 1. The Meiji Restoration as a Constitutional Revolution -- Chapter 2. The First Sino-Japanese War and East Asia -- Chapter 3. The Russo-Japanese War and Modern International Society -- Chapter 4. World War I and the Origin of Sino-Japanese Conflict -- Chapter 5. Transformational Period in Japan-China Modern Relations (1910s-1930s) -- Chapter 6. The Manchurian Incident and Party Cabinets -- Chapter 7. Disarmament Conferences and a Crisis of Diplomacy in the Interwar Period$1 (Bthe Road to World War II -- Chapter 8. The Southward Advance and Going to War with the United States$1 (Bthe Road to World War II -- Chapter 9. US Policy for the Occupation of Japan and Changes to It -- Chapter 10. Law and Politics in the Tokyo Trial -- Chapter 11. Japanese Colonial Rule and the Issue of Perceptions of History -- Chapter 12. Postwar Japan-China Relations -- Chapter 13. The Issue of Historical Perspective from the Post-Heisei Era$1 (BLooking Back at Meiji from the Postwar Period, and Looking Ahead.s
Keywords: Japan -- History; World history; International relations; Political science; History of Japan; World History, Global and Transnational History; International Relations; Political Science